COVID-19 Prevention, Recognition and Home Management Self-Efficacy Scale: A Validity and Reliability Study - ÇAĞAN, Emine Serap; SOLMAZ, Ebru; EKŞİOĞLU, Aysun (Göbeklitepe Medical Science Journal, 2022)
With this work; It is aimed to conduct the Turkish validity and reliability study of the COVID-19 prevention, recognition and home management self-efficacy scale. The data of the research conducted in methodological type were collected by snowball method using online survey method between June and August 2021. In the research, 216 people were reached. Individual identification form and COVID-19 prevention, recognition and home management self-efficacy scale were used to collect data in the study. In order to evaluate the validity of the scale, language, content and predictive validity were performed. In order to evaluate the reliability, invariance over time, cronbach alpha coefficient and item total correlation were made. The Cronbach Alpha internal consistency coefficient of the scale was calculated as 0.90 for the overall scale, and the scale was found to be reliable. In the study, the calculated value for the scope validity index of the scale was obtained as 0.92. As a result of the analysis, the Kaiser-Meyer-Olkin (KMO) test value for sample adequacy was determined to be 0.868. The lowest factor load value of the scale was determined as 0.457 and the highest value as 0.836. As a result of the study, it was determined that the scale is an applicable measurement tool with high reliability and validity, which can be used in Turkish society.